PENGGUNAAN GAYA BAHASA PERBANDINGAN DALAM KUMPULAN PUISI PERJAMUAN KHONG GUAN KARYA JOKO PINURBO (KAJIAN STILISTIKA) - Mansur Hasan; Rafik M. Abasa; Narti Sunarto (Cakrawala Bahasa, 2022)
This study aims to describe how the use of comparative language style in the collection of poetry "Perjamuan Khong Guan" by Joko Pinurbo. This study uses descriptive qualitative research methods. Data collection techniques used are reading techniques, listening techniques and note-taking techniques. The data obtained in this study were obtained from reading and understanding the contents of the poems contained in the collection of poems "Perjamuan Khong Guan" by Joko Pinurbo. The results of this study will be described qualitatively obtained from the analysis of the book collection of poetry "Perjamuan Khong Guan" by Joko Pinurbo as a whole which becomes one part, namely comparative language style. The researcher conducted this study to analyze the comparative language styles that the researchers encountered, including; equation or smile, metaphor, personification, despersonification, allegory, and epithet. The results showed that there were 28 uses of comparative language styles in the collection of poems "Perjamuan Khong Guan" by Joko Pinurbo. The most dominant use of comparative language style is personification of 10 data. Other uses are parables or similes as many as 4 data; metaphor as many as 8 data; despersonification of 3 data; allegory as much as 1 data; and epithet as much as 1 data.